PENGARUH MEDIA PEMBELAJARAN DIGITAL INTERAKTIF BERBANTUAN WEBSITE PREZI TERHADAP MINAT BELAJAR SISWA KELAS IV SEKOLAH DASAR: Penelitian Kuantitatif - Yayan Ariansyah; Hetilaniar; Marleni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the influence of interactive digitallearning media assisted by the prezi website on the learning interest of grade IVelementary school students. This study used the quantitative method of TrueExperimental Design design experiment with pretest-posttest Control GroupDesign. The data collection technique used questionnaires and documentation.Based on the posttest score, the percentage obtained by the control class was69.17% and the experimental class was 85.83%. Hypothesis testing of the data ofthis study used an independent sample t-test with hypothesis testing criteria,namely if the sig < 0,05 then ho is rejected and ha is accepted and if sig>0,05 thenho is accepted and ha is rejected and It was obtained with a value of t count = 2.177 >t table = 1.670 and sig. (2-tailed) = 0.034 <0.05. Based on these calculations, itshows that Ha was accepted and Ho was rejected. The results of the study showthat there is an effect of the use of interactive digital learning media assisted bythe prezi website on the learning interest of grade IV elementary school students.